PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL MODERATING PADA PRODUK TELKOMSEL - Amran, Elsa Fitri; Putri, Suci Mulia; Rizal, Rizal; Sari, Chitra Indah; Mirawati, Mirawati; Nengsih, Ifelda (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2023)
This study aims to determine the effect on product quality and brand image of Telkomsel on customer loyalty with satisfaction as a moderating variable (study of the students of the Faculty of Economics and Islamic Business UIN Mahmud Yunus Batusangkar). The type of research that the author uses is quantitative research. The data collection technique that the researcher used was through a questionnaire. The sample used in this study were 96 respondents. Based on the results of the research, the product quality has an effect on customer loyalty to students of the Islamic Economics and Business Faculty of UIN Mahmud Yunus Batusangkar. Brand Image has an effect on Customer Loyalty to Students of the Faculty of Economics and Islamic Business UIN Mahmud Yunus Batusangkar. Product Quality and Brand Image have a significant effect on Customer Loyalty to Students of the Islamic Economics and Business Faculty of UIN Mahmud Yunus Batusangkar. Product quality has an effect on customer loyalty which is moderated by satisfaction with students of the Islamic Economics and Business Faculty of UIN Mahmud Yunus Batusangkar. Brand Image has an effect on Customer Loyalty which is moderated by Satisfaction of Students of the Faculty of Economics and Islamic Business UIN Mahmud Yunus Batusangkar.